Effect of Shearing on Thermo-Physiological, Behavior, and Productivity Traits of Two Indonesian Local Sheep Breeds - Panjono; Ibrahim, A.; Ngadiyono, N.; Maulana, H.; Atmoko, B. A. (Faculty of Animal Science, IPB University, 2024)
Thin-tailed sheep (TTS) and Fat-tailed sheep (FTS) are local Indonesian sheep breeds characterized by coarse wool. This study aimed to investigate the effects of wool shearing on the thermo-physiological, behavior, and productivity traits of these sheep. Sixteen selected rams were utilized in this study. Animals were assigned to a factorial completely randomized design and divided into two groups (TTS and FTS) and two treatments (sheared and unsheared). The study spanned three months under controlled conditions. Variables observed included environmental conditions, thermo-physiological parameters (respiratory rate/RR, pulse rate/PR, rectal temperature/RT, and heat stress index/HSI), sheep behavior (feeding duration, drinking frequency, rumination duration, urination frequency, defecation frequency, standing duration, and lying duration), and sheep productivity (feed intake, average daily gain/ADG, and feed conversion ratio/FCR). Data were analyzed using two-way ANOVA. Throughout the study, average temperature and humidity ranged from 25.13-30.48 oC and 64.50%-91.67%, respectively. Wool shearing significantly influenced (p<0.05) sheep’s thermo-physiological, behavior, and productivity traits. These effects were consistent across sheep breeds, with no significant differences noted. Wool shearing significantly reduced (p<0.05) RR, PR, and RT, while the impact on average HSI was not significant. Additionally, sheared sheep exhibited increased (p<0.05) feeding, rumination, standing duration, and higher defecation frequency. Conversely, drinking frequency, urination frequency, and lying duration decreased in the sheared sheep group. Moreover, the sheared sheep demonstrated higher (p<0.05) feed intake and ADG, leading to a reduced (p<0.05) FCR compared to the unsheared group. In conclusion, shearing is a recommended practice for coarse wool-type sheep in tropical environments. This technique does not induce stress and enhances their thermo-physiological, behavior, and productivity traits.